Talking – Listening – Getting Involved: Democracy-didactical impulses for dialogical learning in primary education (Pedagogical Horizons, 2025)
Sustainable political education goes beyond mere factual knowledge and enables immersion in the three dimensions of politics (Krammer, 2008; Kühberger, 2016). In practice, however, teachers fear influencing their own students (Larcher & Zandonella, 2014) or avoid teaching history in general studies (Hofmann-Reiter, 2021). According to Krösche (2024, p. 45), gaps in teacher training contribute to the low priority given to political education in primary schools. Lange et al. (2024) also emphasise the underrepresentation of the topic in the national education report. This gap should be closed. This article builds on the publication ‘Die Qual der Wahl – Kompetenzorientierte Demokratiebildung in der Volksschule’ (Mansberger, 2025) and focuses on learning through dialogue in order to ultimately create awareness of peace and democratic values. Senghaas' (1995) civilisational hexagon forms the theoretical framework and shows practical implementation possibilities for all sub-areas in the teaching context. A competence-oriented lesson overview of participatory and dialogue-oriented forms of learning highlights the central role of communication. A didactic analysis shows that by talking and listening together, pupils learn to represent their own points of view and recognise other perspectives. Finally, this article discusses professional development opportunities for prospective teachers to promote a sustainable democratic school culture.
Keywords: democracy education; political didactics in primary education; participation; communication; teacher training